Altitudinal variation in morphological traits of Pinus patula populations from Oaxaca state, Mexico, and its use in the zoning - Viveros-Viveros, Héctor; Camarillo-Luna, Alfredo R; Sáenz-Romero, Cuauhtémoc; Aparicio-Rentería, Armando (Bosque (Valdivia), 2017)
Populations of forest species with a distribution across altitudinal gradients tend to differ in morphology, allowing zoning for conducting seed movement. The pattern of variation is not known to many Mexican pine species. The altitudinal pattern of morphological variation was explored in needles, cones and seeds of 13 Pinus patula populations sampled from the Native Indian Community forest of Ixtlán de Juárez, Oaxaca, Mexico, along an altitudinal gradient (from 2,450 to 3,050 m a.s.l); needles and cones being collected every 50 m of altitudinal step. Significant differences among populations and among trees within populations were detected for all the evaluated traits. The correlation was positive between the altitude of origin of populations and keel width, cone width and leaf-sheaths length; whereas it was negative between needle length and altitude of origin of populations. Using the phenotypic variation of the needle length we suggest a provisional delineation of two altitudinal seed zones (zone I: 2,150 to 2,600 m; zone II: 2,600 to 3,050 m), as a guideline to decide seed movements in reforestation programs. Altitudinal zones obtained in this work have wider altitudinal range per zone (meaning a more liberal seed movement) than the one obtained from twenty four-months-old seedling height growing in a provenance test, and show that it is possible to make provisional altitudinal zoning based on patterns of phenotypic variation across environmental gradients.